Affective Touch in Preterm Infant Development: Neurobiological Mechanisms and Implications for Child-Caregiver Attachment and Neonatal Care - Valentina Lucia La Rosa; Alessandra Geraci; Alice Iacono; Elena Commodari (MDPI AG, 2024)
Background/Objectives: Affective touch is crucial in infant development, particularly in regulating emotional, cognitive, and physiological processes. Preterm infants are often deprived of essential tactile stimulation owing to their early exposure to the external environment, which may affect long-term developmental outcomes. This review aimed to examine the neurobiological mechanisms of affective touch and highlight effective interventions, such as skin-to-skin contact (SSC) and kangaroo care (KC), to promote development in preterm infants. Methods: This review summarizes recent studies in the literature on affective touch, the role of C-tactile fibers, and the effects of tactile interventions in neonatal care. Studies were selected based on their relevance to the care and development of preterm infants, with a focus on physiological and neurodevelopmental outcomes. Key interventions, including SSC and massage therapy, are discussed in relation to their effectiveness in the neonatal intensive care unit (NICU). Results: The results suggest that affective touch, mainly through activation of tactile C-fibers, improves caregiver-infant bonding, reduces stress responses, and supports neurodevelopment in preterm infants. Interventions such as SSC and KC have also been shown to improve physiological regulation in these infants, including heart rate, breathing, and temperature control while promoting emotional regulation and cognitive development. Conclusions: Affective touch is a key component of early development, particularly in preterm infants admitted to the NICU. Integrating tactile interventions such as SSC and KC into neonatal care practices may significantly improve long-term developmental outcomes. Future research should explore the epigenetic mechanisms underlying affective touch and further refine tactile interventions to optimize neonatal care.